A clinical snapshot: Do elite swimmers experience more upper respiratory illness than nonathletes? - Fricker, P. A.; Gleeson, M.; Flanagan, A.; Pyne, D. B.; McDonald, W. A.; Clancy, R. L. (Clinical Exercise Physiology, 2000)
Purpose: To determine whether elite athletes experience more upper respiratory illness (URI) than the general community. Methods: All medical files of swimmers in residence at the Australian Institute of Sport (AIS) from 1988-98 inclusive were reviewed, and all cases of URI were documented. Each reported episode of URI was considered only once for the purposes of analysis. An attempt was made to distinguish viral from bacterial illness. A community survey of URI in Australia published in 1978 was used for comparison. Results: Ninety-seven swimmers were reviewed and compared with 9,014 members of the Australian community. Male swimmers experienced an average of 2.5 episodes of URI per year, female swimmers 3.1 episodes per year. The mean for all swimmers was 2.7 episodes per year. The difference in means between male and female swimmers is not statistically significant. The incidence of "the common cold" in the community was estimated at 3.0 episodes per person per year for age decile 10-19 yr and 2.4 episodes per person per year for age decile 20-29 yr. Conclusions: Elite swimmers in Australia do not appear to experience more URI than the broad Australian community. Careful prospective studies are needed.